Peran Tokoh Agama Dalam Menanamkan Filosofi Perilaku Militansi Beragama Umat Hindu Kaharingan Di Kecamatan Kahayan Tengah Kabupaten Pulang Pisau - Wayan Gepu; I Gede Dharman Gunawan; I Ketut Subagiasta; Roy Wentas (Jayapangus Press, 2022)
This study aims to describe and analyze how the role of religious leaders in instilling the philosophy of religious militancy behavior of Kaharingan Hindus in Kahayan Tengah District, Pulang Pisau Regency. Religion as a belief adhered to by Hindus and used as a guide in carrying out various activities, as well as a torch in carrying out a life full of its complexities. The existence of religion requires the role of religious institutions in fostering people who support development. In line with this, it is necessary to have the role of religious leaders in instilling the philosophy of religious militancy behavior of Kaharingan Hindus. Strategic efforts and roles are needed in providing optimal service and guidance for Kaharingan Hindus. Based on the results of observations in the field there is still a lack of understanding of religious teachings, especially Hindu Kaharingan children who study their religious teachings well and build strong beliefs and foster religious militancy for the younger generation of Hindu Kaharingan. So it is important the role of religious leaders in instilling a philosophy of religious militancy behavior for Kaharingan Hindus. This study uses a qualitative method. The results of this study include (1) The Role of Religious Leaders in Instilling the Philosophy of Religious Militancy Behavior of the Kaharingan Hindus including the Role of Religious Figures in Increasing Religious Understanding, Increasing Religious Development, Role for the Young Generation of Hindu Kaharingan, and for Women. (2) The meaning of the Philosophy of Religious Militancy Behavior of Kaharingan Hindus in Kahayan Tengah District, Pulang Pisau Regency includes, Behavior of Religious Firmness, Behavior of Religious Stability, Behavior of Religious Stability, and Behavior of Religious Consistency.